2018
DOI: 10.1002/bies.201800018
|View full text |Cite
|
Sign up to set email alerts
|

May the Fittest Protein Evolve: Favoring the Plant‐Specific Origin and Expansion of NAC Transcription Factors

Abstract: Plant-specific NAC transcription factors (TFs) evolve during the transition from aquatic to terrestrial plant life and are amplified to become one of the biggest TF families. This is because they regulate genes involved in water conductance and cell support. They also control flower and fruit formation. The review presented here focuses on various properties, regulatory intricacies, and developmental roles of NAC family members. Processes controlled by NACs depend majorly on their transcriptional properties. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 190 publications
(172 reference statements)
0
40
0
Order By: Relevance
“…NAC genes are recognized to be largely involved in many developmental and growth processes, such as the differentiation of major organs [81]. Our study highlighted genes that are preferentially expressed in the leaf (16) or in the grain (7) regardless of the genotype, the grain developmental stage, or the field conditions.…”
Section: Discussionmentioning
confidence: 84%
“…NAC genes are recognized to be largely involved in many developmental and growth processes, such as the differentiation of major organs [81]. Our study highlighted genes that are preferentially expressed in the leaf (16) or in the grain (7) regardless of the genotype, the grain developmental stage, or the field conditions.…”
Section: Discussionmentioning
confidence: 84%
“…The maximum numbers of the DLN repressors of rice belonged to C2H2 zinc finger family, with MYB, NAC, AP2 and PHD as other prominent families (Tables S1–S3). We have previously reported the presence of this motif in ZOS TFs [30] and have also shown NAC TFs to act as repressors [31,32]. AP2/ERF repressors having L/FDLNL/F(x)P as the motif essential for repression, were the first ones to be identified [33].…”
Section: Resultsmentioning
confidence: 99%
“…The NAC family are plant-specific transcription factors. Previous studies [15,26,75] have shown that NACs are involved in plant growth and development, which pattern organs, biotic stress, and abiotic stress. However, current research on NAC transcription factors is mainly focused on model plants.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous NAC domain proteins have been implicated in plant biotic stress and abiotic stress, such as fungi, bacteria, insects, drought, salinity, and cold and mechanical wounding [14,26]. The AtNAC2 gene from A. thaliana is a transcription factor downstream of ethylene and auxin signaling pathways, which plays an important role in salt stress response [27].…”
Section: Introductionmentioning
confidence: 99%